18π‐Electron Tautomeric Benziphthalocyanine: A Functional Near‐Infrared Dye with Tunable Aromaticity1. (4th June 2014) - Toriumi, Naoyuki; Muranaka, Atsuya; Hirano, Keiichi; Yoshida, Kengo; Hashizume, Daisuke; Uchiyama, Masanobu
Abstract Dihydroxybenziphthalocyanine 1, with bulky aryloxy groups, has been synthesized and characterized by X‐ray crystallography, NMR and UV/Vis‐NIR spectroscopy, and theoretical calculations. Macrocycle 1 is the first example of an aromatic benziphthalocyanine with an 18π‐electron structure, and was found to exist as an equilibrium mixture of weakly aromatic and strongly aromatic tautomers. The aromaticity and near‐IR absorption can be controlled by chemical modification at the reactive resorcinol moiety and by variation of the solvent.